Marine Seaweed Polysaccharides: An Insight into Biological Activities and Biomedical Applications - B., Jegadeshwari; S.D., Saraswathy (Natural Products Journal, The, 2024)
Natural products from various sources play a major role in the healthcare sector, mainly in the pharmaceutical, cosmetic, agro and medical divisions. Polysaccharides are one of the important biomacromolecules present in higher plants, animals, fungi and algae, and aid in the growth and development of an organism. They play a vital role in regulating and maintaining cellular homeostasis in all forms of life. They are considered bioactive polymers and possess promising beneficial effects on human health without any harmful side effects. Among different biopolymers, polysaccharides have gained greater attention in the area of natural products and biomedical research due to their unique physio-chemical properties, bioactivities and health-promoting effects. The molecular structure of the polysaccharides is highly complex, depending on their origin and the structural diversity. Carbohydrate polymers differ largely based on their molecular weight, composition, functional derivatives, pattern of glycosidic linkages and degree of polymerization. In recent years, seaweed polysaccharides have been identified in large numbers and are effectively used by the food and biotechnology industries for the production of nutraceutical and pharmaceutical products. Several researches have demonstrated the biological activities of seaweed polysaccharides such as antioxidant, antiviral, hypoglycemic, antidiabetic, antitumor and immunomodulatory. Moreover, there has been a substantial increase in the utilization of natural polymeric biomaterials in the biomedical field. This review summarizes the diverse biological effects of polysaccharides derived from different types of seaweeds as well as their biomedical applications. The information reviewed here provides an insight into the biopotential efficiency of algal-based polysaccharides, further help in the development of novel pharmaceutical and biomedical products.
Keywords: seaweed polysaccharides